Overshooting and Dollarization in the Democratic Republic of the Congo - Beaugrand, Philippe (Washington, D.C. : International Monetary Fund, 2003)
The paper develops an interpretation of volatile exchange rate movements in a dollarized economy with very high rates of inflation. Differences between the rate of inflation and currency depreciation (over- or undershooting of the exchange rate) are seen as a proxy for changes in the relative demand for domestic and foreign currency. A simple model is calibrated for the Democratic Republic of the Congo in the 1990s and is used to derive estimates of the rate of dollarization.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet